Peculiarities of using yoga therapy and kinesiotaping in physical therapy of patients with ankylosing spondylitis - Filatova, Alona; Antonova-Rafi, Yulia (The Ukrainian Scientific Medical Youth Journal, 2023)
numerous publications indicate that the quality of life of patients with ankylosing spondy- litis (AS) is poor due to a combination of symptoms that limit the functional abilities of patients: stiff- ness of movements (91% of patients), pain (82%), increased fatigue (61%), poor sleep (55%), anxiety about the future (51%). The aforementioned characteristics of ankylosing spondylitis account for a high incidence of permanent disability, ranging from 24% to 81% [1]. This disease is currently incurable, but ankylosing spondylitis and its destructive effects on the spinal column can be slowed by methodsand means of physical therapy, maintaining the mobility of the spine and joints and avoiding further progression of the disease. One such means of physical therapy is yoga therapy and kinesiotaping, whose effectiveness has been proven in this study. The article deals with the main problems of spinal mobility in patients with ankylosing spondylitis and presents the methodology of physical rehabilitation for this contingent of patients in the post-hospital period, which is developed by adding yoga therapy and kinesiotaping to the classical physical therapy program of patients with ankylosing spondylitis. The proposed methodology helps to slow down the progression of this pathology, maintain mobility in allparts of the spinal column, reduce pain syndrome and morning stiffness in the lumbar spine. In order to evaluate the effectiveness of the developed physical therapy program for patients with ankylosing spondylitis, a study of 8 patients was carried out and observed at the medical center of physical reha- bilitation «Algorithm Health» in Kiev.